Mathematics as a gendered subject: a deeper insight into students' attitudes in Irish post-primary schools. Issue 4 (2nd October 2021) - O'Rourke, Iseult; Prendergast, Mark
Abstract : This study examines gender differences in students' attitudes to mathematics in Irish post-primary schools. Large-scale international assessments have shown the achievement gap between boys and girls to be narrowing in recent years, particularly in lower post-primary education. However, women and girls remain significantly under-represented in advanced level mathematics courses and STEM careers. The current research aims to contextualise this state of inequity, providing a deeper understanding of gendered attitudes to mathematics in Ireland today. To this end, Irish data from the 2015 Trends in International Mathematics and Science Study is further analysed, focusing specifically on the student background questionnaire. Various aspects of students' attitudes to mathematics are investigated, including their interest in mathematics, views on mathematics class, confidence and mathematical self-concept, and perceived importance of mathematics as a subject. The findings show consistent and significant attitudinal gender differences. These differences were generally strongest regarding confidence and self-concept, and attitudes to mathematical problem-solving. Differences regarding attitudes to mathematics lessons were small to negligible.